2020
DOI: 10.1098/rspb.2019.2251
|View full text |Cite
|
Sign up to set email alerts
|

Joining a group diverts regret and responsibility away from the individual

Abstract: It has recently been proposed that a key motivation for joining groups is the protection from the negative consequences of undesirable outcomes. To test this claim, we investigated how experienced outcomes triggering loss and regret impacted people's tendency to decide alone or join a group, and how decisions differed when voluntarily made alone versus in group. Replicated across two experiments, participants ( n = 125 and n = 496) selected whether to play alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…Our findings showed that people’s subjective reports of responsibility varied according to social context, with greater responsibility reported when making decisions privately compared to when making decisions with others. This is in line with previous studies that show that people feel less control, responsibility and regret when acting with others [3,14,16,17]. Reported responsibility varied with group size, with more responsibility reported in Dyads vs in a Group of five.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings showed that people’s subjective reports of responsibility varied according to social context, with greater responsibility reported when making decisions privately compared to when making decisions with others. This is in line with previous studies that show that people feel less control, responsibility and regret when acting with others [3,14,16,17]. Reported responsibility varied with group size, with more responsibility reported in Dyads vs in a Group of five.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, when people assign credit to contributors in a team, they tend to overestimate their own contribution and over attribute a team's success to their own abilities, effort and merit [2]. Conversely, when outcomes are poor, the collective context allows us to distance ourselves from regret [3] and offload blame onto others [4]. Teams are more likely to violate rules than individuals [5] and, correspondingly, people find it harder to punish groups (vs individuals) that have violated a social norm [4].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking elevated accuracy [ 46 ] is perhaps the most popularly recognised motive but only one among many other motives. Other motives include diffusion of responsibility and regret [ 47 ] and equality [ 2 ]. Future research could help determine whether and to what extent our participants were driven by these various motives.…”
Section: Discussionmentioning
confidence: 99%
“…In many everyday situations, whether in the workplace or with our family and friends, responsibility for outcomes is shared among several individuals because these outcomes stem from collective decisions. Collective decisions can reduce the burden of individual responsibility 3,4 , because people feel less responsible when performing an action as a group than when acting alone [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%